Why Are Abusive Supervisors Abusive? A Dual-system Self-control Model - Liang, Lindie H.; Lian, Huiwen; Brown, Douglas J.; Ferris, D. Lance; Hanig, Samuel; Keeping, Lisa M. (Academy of Management Journal, 2016)
Building on prior work which has shown that abusive supervision is a reaction to subordinates’ poor performance, we develop a self-control framework to outline when and why supervisors abuse poor-performing subordinates. In particular, we argue that poor-performing subordinates instill in supervisors a sense of hostility toward the subordinate, which in turn leads to engaging in abusive supervision. Within this self-control framework, poor performance is more likely to lead to abusive supervision when (a) the magnitude of the hostility experienced is higher (e.g., for those with a hostile attribution bias), or (b) the translation of hostility into abusive supervision is unconstrained (e.g., for those who are low in trait mindfulness). In two experimental studies with full-time supervisors where we manipulated the independent variable (Study 1) and the mediator (Study 2), and in a multi-wave and multi-source field study with data collected from supervisor–subordinate teams (50 supervisors and 206 subordinates) at two time points (Study 3), we found overall support for our predictions. Implications for how to reduce the occurrence of abusive supervision in the workplace are discussed.